FENITE HALOS OF LINEAR CARBONATITE MASSIFS: IDENTIFICATION CRITERIA AND DETERMINATION OF GEOLOGICAL STRUCTURE - Shnyukov, S.; Lazareva, I.; Nykanorova, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this paper, there have been contrasted the morphological features of fenite halos associated with the two types of carbonatite massifs: linear – Chernigovka, Dubravinka, Penchenga (Ukrainian Shield, Voronezh crystalline massif and Yenisei Ridge, respectively) and central – Alno, cape Turiy (Baltic Shield). It has been found that, in contrast to the isometric fenite halos of the central type massifs, fenite halos of linear massifs generally show irregular thickness (or even rare occurrence) and morphological asymmetry best expressed in the case of the flat-dipping of carbonatite bodies. There have been determined the geochemical features of the most common accessory minerals (zircon, apatite, sphene) from zonal fenite halos of linear type massifs. The identified distribution patterns for trace elements in accessory zircons from the fenite halo rocks of Chernigovka carbonatite massif may be applied as a criterion when classifying metasomatic rocks as fenites. The distribution features of trace elements in apatites and sphenes from fenite halo rocks are the key to identifying the contrast types of host rocks, as well as estimating their transformation level, and they clearly illustrate the composition convergence of the newly formed accessory minerals. The results obtained provide motivation for the use of data on trace elements composition of the most common accessory minerals from fenite halos in a complex of forecasting and prospecting criteria. These data are essential in describing the morphology of the halos, revealing and mapping their zonation, and optimizing the fenite nomenclature.
Keywords: carbonatites; fenitization; trace elements; accessory minerals; zircon; apatite; sphene; Ukrainian Shield; Baltic Shield; Yenisei Ridge; Voronezh crystalline massif